INFORMATIONAL REQUIREMENTS AND ENVIRONMENTAL PROTECTION - Karen Morrow (Oxford Handbook of Comparative Environmental Law, 2019)
The book which this chapter is drawn from seeks to develop a framework that will imptove the understaning, research and analysis of comparative enviornmental law. This chapter forms part of the strand of the larger project that focuses on what the editors identify as its core component, analysis of the 'fundamental systems underpinning the diversity observed across countries'. The chapter offers a novel analysis of information framed around question sof power and control, looking principally at still domanint state-centred regimes (including an early treatment, using a rarely availabe international comparative law approach, of the drafting process and draft content of the ECLAC Convention) but also extending its reach to the evolving roles of other actors, including business and civil society (the latter in particular rainisng both challenegs and nascent possibilities in the context of big data).